ADAPTASI KULTURAL MASYARAKAT MULTIETNIS TEPIAN SUNGAI KAPUAS KOTA PONTIANAK DALAM KONTEKS PENDIDIKAN DAN PEMBELAJARAN - Muhammad Syaifulloh; Basuki Wibowo (Refleksi Edukatika)
This study aims to determine and understand the cultural adaptation and methods of the multiethnic community on the banks of the Kapuas River in Pontianak City in the context of education and learning.